(83-x)+(5x+11)=10

Simple and best practice solution for (83-x)+(5x+11)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (83-x)+(5x+11)=10 equation:


Simplifying
(83 + -1x) + (5x + 11) = 10

Remove parenthesis around (83 + -1x)
83 + -1x + (5x + 11) = 10

Reorder the terms:
83 + -1x + (11 + 5x) = 10

Remove parenthesis around (11 + 5x)
83 + -1x + 11 + 5x = 10

Reorder the terms:
83 + 11 + -1x + 5x = 10

Combine like terms: 83 + 11 = 94
94 + -1x + 5x = 10

Combine like terms: -1x + 5x = 4x
94 + 4x = 10

Solving
94 + 4x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-94' to each side of the equation.
94 + -94 + 4x = 10 + -94

Combine like terms: 94 + -94 = 0
0 + 4x = 10 + -94
4x = 10 + -94

Combine like terms: 10 + -94 = -84
4x = -84

Divide each side by '4'.
x = -21

Simplifying
x = -21

See similar equations:

| (3x+2)(2x-1)=-(3x+1) | | 7y+9=6y-2 | | 645-07-04-00-00_files/i0090000.jpg | | (83-x)=180 | | 3=x/3.3 | | (0,29x)/(0,4-0,4x^2,39) | | x/6=3/4 | | x^8+254x^4+1=0 | | (5x+11)=180 | | (M-9)+6=4(m-2)-2(m-6) | | 2x+13=-5x-7x | | 18a/6 | | (7+5i)+(5i)= | | (x-2x/100)*60/100*70/100=7203 | | (5x+11)=360 | | (-8i)-(3i)= | | 4d=1/3 | | x+(3x+15)=135 | | 256x^2=-176 | | Y+5-6y=17-2y | | 1.2c=0.6 | | (3i)-(I)= | | 3d+5d+9d-8= | | f(x)=6x^3+11x^2-10x | | (8j-9)=14 | | 6=3/5w | | 4(d+3)= | | 2w-3=2w | | a+5a+4b= | | 1.6x=2.5y+2 | | 7v/6=42 | | 7+9x=180 |

Equations solver categories